Pentingnya Kolaborasi 4 Keterampilan Dasar Bahasa Inggris Mengunakan Drill Method bagi Siswa LKP YHSUA Training Institute Self-Development - Manase Halitopo; Napius Kogoya; Laura Sansa Maitimu; Andinus Yanengga; Barton Wenda; Lemurah Wenda; Amelia Kaisepo; Febronius D Naja; Piter Mabel (Lembaga Pengembangan Kinerja Dosen, 2025)
LKP YHSUA Training Institute Self-Development is one of the course places for the Papuan people, which is located in the Pikhe, Wamena. This course provides places for Papuan people to develop their potential by offering courses and direct practices in the field. In contrast, one of the problems LKP YHSUA Training Institute Self-Development students face is a lack of understanding and motivation in learning English. As a solution to this problem, a Community Service socialization is designed for the collaboration of four basic English skills. The purpose of this socialization is to improve the students’ four English skills at LKP YHSUA Training Institute Self-Development. The method used in this socialization is the drill method. As a result of using the drill method, students of LKP YHSUA Training Institute Self-Development could develop their basic skills in English such as be able to listen, to speak, to read, and to write, even though they are not so passive in improving their skills, the drill method has encouraged their interest in using the four English skills.